Trading book request monitoring tool project completion report - Simon, Jennifer P.; Zamora, Dr. Elvira (Quezon City University of the Philippines Diliman, 2010)
This project involves the setting up of a monitoring tool with a macro that will be used to track the status of the various Trading Book Request requests for use of the BPS Bank- Trading Book Request Team.
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: Trading companies -- Accounting -- Automation; Book request monitoring tool